High-capacity image steganography algorithm combining image encryption and deep learning - Xiaoyuan YANG; Xinliang BI; Jia LIU; Siyuan HUANG (Tongxin xuebao)
Aiming at the problem that the residual image of cover image and carrier image in the high-capacity image steganography scheme based on deep learning will expose the secret image, a high-capacity image steganography scheme combining image encryption and deep learning was proposed.An image feature extraction method was used, so that the features extracted from the cover image were consistent with the features extracted from the carrier image.Before the image steganography, the sender extracted features from the cover image as a key to encrypt the secret image.After the extractor extracted the encrypted secret image, the features were extracted from the carrier image as a key to decrypt the secret image.The experimental results show that the attacker cannot find the information of the secret image from the residual image, and the frequency of key transmission is lower, and the security of the algorithm is improved.